The effectiveness of communication skills in managing and planning music events among music society members of the UiTM Faculty of Music / Muhammad Azamuddin Aziz - Aziz, Muhammad Azamuddin (2019)
Communication is our daily routine. We communicate every day to send and receive message with other people. Some message are interrupt by noise or communication barriers and effect the message. In workplace, communication is very important to communicate with other employee and also manager. There are also a few barriers of communication in workplace especially work in group. Music society member of Faculty Music UiTM Shah Alam need to work in group for manage and plan their events. This situation involve communication skills for them to communicate with members and also other people that involves. To communicate with members and other people, a few of communication skills that being used to send and receive messages. Every person have their suitable communication skills that effective to them and also with other people. Barriers of communication skills always occurs in this situation especially in group. To avoid problems in manage and plan events, members need to solve the barriers. The successful of the events depends on the teamwork and management of the organizations. Effectiveness of communication skills related to the successful of the events. This research was qualitative method by using random sampling. Interview sessions that involved 15 students among music society members in Faculty Music of UiTM Shah Alam was carried for this research. It is hope that the study can contribute to the knowledge of communication skills to manage and plan events among society member in Faculty of Music UiTM Shah Alam.